Ampliação da distribuição geográfica de três caranguejos majóideos (Crustacea, Decapoda, Brachyura) na costa do Estado de São Paulo, Brasil - de Vasconcelos Camargo, FláVio [UNESP] (2010)
This study reports range extensions of three species of crabs to the northern coast of the state of São Paulo. The species obtained were Inachoides forceps, Microphrys antillensis and Mithraculus sculptus. Recent new records of marine species in Brazilian waters illustrate the importance of continuous investigations on the biodiversity of subtidal rocky bottoms.